Size reduction of gold nanoparticles by pulsed laser ablation and reirradiation in water media - Pichitchai Pimpang (2018)
Gold nanoparticles (Au NPs) were prepared by using pulsed laser ablation with and without cover slide. The cover slide was used to confine atoms/ions in order to reach supersaturation condition. The obtained Au NPs were investigated by UV-vis spectroscopy, transmission electron microscopy (TEM), and zeta potential measurement. The absorbance spectra exhibited its absorption peak at around 520 nm for both Au NPs ablating with and without cover slide. It was found that Au NPs ablating with cover slide exhibited smaller size and size distribution (10.6 ± 5.9 nm) than those of without cover slide (34.1 ± 21.5 nm) at laser power of 5.00 mJ/pulse. This is due to supersaturation effect and re-irradiation effect caused by cover slide that trapped atoms/ions of gold and trapped Au NPs, respectively. Also, the zeta potential of Au NPs had a negative value suggesting negative surface charge. The lowest zeta potential was observed for Au NPs ablating with cover slide at 5.00 mJ/pulse and it was in consistent with an observation of the highest pH value. In addition, the Au NPs ablating with cover slide at 5.00 mJ/pulse showed the least change with time indicating the most stable Au NPs which was in consistent with the lowest zeta potential results. Thus, pulsed laser re-irradiation could be used for size reduction of Au NPs prepared by pulsed laser ablation in water media. © (2011) Trans Tech Publications.